A generalized predictive control for remote cardiovascular surgical systems. (September 2020) - Hu, Zhi; Zhang, Junfeng; Xie, Le; Cui, Guohua
Abstract: Robot-assisted cardiovascular surgery is used to avoid surgeon suffering from X-ray radiation and relieve fatigue caused by long-time standing wearing protective clothing. Its remote surgery can alleviate the lack of experienced doctors in remote areas. Due to the existence of time-delay phenomena, flexible deformation and nonlinearity of interventional instruments, it is difficult to ensure system transparency. This paper analyzes the evaluation index of system transparency. A generalized predictive control (GPC) is developed to suppress the effect of time-varying delay and parameter identification error. Moreover, a terminal sliding mode controller (SMC) is designed to improve the robustness of the system under consideration. Simulation results are provided to show that the proposed control strategy can improve transparency of the remote vascular interventional surgery system. Highlights: A GPC is developed to eliminate the effect of time delay variation and parameter identification error. The proposed control system possesses better response ability and robustness. Compared to other state-of-the-art controller, the proposed method can improve system transparency.